Pulsatilla nigricans Störck (Ranunculaceae Juss.) на Київському плато: поширення; умови місцезростань, стан і структура ценопопуляцій у лучно-степових угрупованнях; охорона - Gritsenko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The results of the study of Pulsatilla nigricans Störck (Ranunculaceae Juss.) spreading on Kyiv plateau are cited. Ecological and coenotical conditions of habitats, state and structure of cenopopulations of P. nigricans in the meadow steppes communities of region are characterized. The protection of P. nigricans on Kyiv plateau in situ and ex situ is considered. Recommendations for botanical reservations creation are elaborated.